2021
DOI: 10.1097/yco.0000000000000709
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on gambling and gambling disorder: emerging data

Abstract: Purpose of review The lockdown response to the COVID-19 pandemic has significantly impacted commercial gambling in many jurisdictions around the world. The goal of this review is to systematically identify and describe the survey data and findings to date examining the effect on individual gambling and gambling disorder. Recent findings Of the 17 publications meeting inclusion criteria, the majority reported cross-sectional assessments ( n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
94
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 27 publications
(47 reference statements)
11
94
0
9
Order By: Relevance
“…Among those who continued to gamble, significant decreases were detected on all gambling engagement measures: number of gambling types engaged in, gambling frequency, time spent in gambling sessions, as well as a significant reduction in gambling related financial losses. These reductions parallel those found in other surveys in Canada and elsewhere (Hodgins & Stevens, 2021 ). In light of the fact that the majority of the sample at baseline report engaging in gambling activities via land-based only platforms these decreases make intuitive sense—gambling engagement will decrease while legal land-based platforms are restricted or entirely inaccessible.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Among those who continued to gamble, significant decreases were detected on all gambling engagement measures: number of gambling types engaged in, gambling frequency, time spent in gambling sessions, as well as a significant reduction in gambling related financial losses. These reductions parallel those found in other surveys in Canada and elsewhere (Hodgins & Stevens, 2021 ). In light of the fact that the majority of the sample at baseline report engaging in gambling activities via land-based only platforms these decreases make intuitive sense—gambling engagement will decrease while legal land-based platforms are restricted or entirely inaccessible.…”
Section: Discussionsupporting
confidence: 88%
“…An editorial in Addiction underscored the urgency of research and surveillance of the pandemic effects on addictive behaviors (Marsden et al, 2020 ). A recent review found 11 published and unpublished cross sectional surveys in which participants were asked to compare their gambling prior to and during the COVID lockdown (Hodgins & Stevens, 2021 ). These surveys report overall reduction in gambling in their samples but also that a small subpopulation described increased gambling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many individuals have seen their free time (and time at home) increased during the lockdowns and some have resorted to online gambling as a means to cope with boredom, social isolation, and psychological distress (Wardle et al, 2021 ). Although the actual impact of the COVID-19 outbreak on problem gambling remains to be determined (Gainsbury et al, 2020 ; Hodgins & Stevens, 2021 ; Zamboni et al, 2021 ), the evidence suggests that there are more active online gamblers than before the pandemic (Auer & Griffiths, 2021 ). In Spain, where the current study was carried out, registered online gamblers increased by 8.36% from 2019 to 2020 (Dirección General de Ordenación del Juego, 2021 ).…”
Section: Introductionmentioning
confidence: 99%